The Influence of Capital and Labor Factors on Coffee Production In The Regency of Pesisir Selatan, West Sumatra Province - Fitri Ayu; Firwan Tan; Febriandi Prima Putra (Universitas Batanghari Jambi, 2022)
Coffee has been a leading commodity in Pesisir Selatan Regency however it has not been able to provide high economic value for the community. This is due to coffee production which has decreased during the 2016-2020 period. So as an effort to improve, it is necessary to optimize production factors in order to maximize production. This study aims to analyze the factors that influence coffee production in Pesisir Selatan Regency. This study uses primary data which was analyzed descriptively quantitatively using the Cobb-Douglas production function and multiple linear regression (OLS) processing methods for 113 respondents who were taken by purposive sampling. The variables of capital and labor will be analyzed to see their effect on coffee production. Based on the results of the study, it was found that partially the capital variable had a significant effect on the amount of coffee production, while the labor variable had no significant effect. But together the variables of capital and labor affect the coffee production produced in Pesisir Selatan Regency.